Menimbang kesahihan hadis dalam perspektif Shi'ah Ima - Noorhidayati, Salamah; Astuti, Robitoh Widi; Saepuloh, Ahmat (LPPM IAIN Kediri, 2020)
The study of Shi’ah is always interesting to be discussed and researched, both in terms of theology and scientific concepts. Shi’ah Ima>miyah whose entire religious building pivots on the Imam, of course, has implications in many ways, including in the hadith field. The position of the Imam as one source of teaching has an impact on the conception of the hadith and its validity criteria. The question is, whether in determining the quality of traditions among Shi’ah refers to the validity of this tradition? How is the process of criticism of hadith that used? And what about the results of the validity test? This article aimed to test the consistency between the validity of the hadith that has been formulated with the implementation process in determining the quality of the hadith. This research is a literature study in the hadith field. Data was collected from various literary works, articles, and other forms of information that were scientific and had a close relationship with the themes discussed. The data obtained were analyzed objectively by comparing one opinion with another, the conclusion was obtained from the research problem. This study concludes: first, in determining the quality of the hadith, the Shi’ah sect is guided by the validity of the formulated Hadith. Second, the assessment of the validity of the hadith through the process of criticism of the narrators in sanad by using their version of the book rija> l al-hadi>th. However, because the Shi’ah believes that everything sourced from the Imam can be accepted as hujjah, then criticism of the matan is not carried out on the condition that the quality of the sanad is valid. Third, the implementation of the validity of the hadith has implications for the quality of multilevel hadith, namely sahi>h, hasan, muwaththaq and da’i>f. Kajian tentang Shi’ah selalu menarik untuk dilakukan, baik dari aspek teologi maupun konsep keilmuannya. Shi’ah Ima>miyah yang seluruh bangunan keagamaannya berporos pada Imam, tentunya berimplikasi dalam banyak hal, termasuk dalam bidang hadis. Posisi Imam sebagai salah satu sumber ajaran berdampak pada konsepsi hadis dan kriteria kesahihannya. Yang menjadi pertanyaan adalah, apakah dalam penentuan kualitas hadis di kalangan Shi’ah mengacu kepada kaedah kesahihan hadis ini? Bagaimana proses kritik hadis yang mereka gunakan? Dan bagaimana hasil uji kaedah kesahihan tersebut?. Artikel ini bertujuan untuk menguji konsistensi antara kaedah kesahihan hadis yang telah dirumuskan dengan proses implementasinya dalam penentuan kualitas hadis. Penelitian ini merupakan studi kepustakaan di bidang ilmu hadis. Data dikumpulkan dari beberapa literatur berupa buku, artikel, dan sumber lain yang otoritatif dan memiliki relevansi dengan tema kajian. Data yang diperoleh dianalisis secara objektif dengan menggunakan metode komparatif, untuk kemudian diambil konklusinya. Penelitian ini menyimpulkan: pertama, dalam penentuan kualitas hadis, sekte Shi’ah berpedoman pada kaedah kesahihan hadis yang telah dirumuskan. Kedua, penilaian kesahihan hadis melalui proses kritik para perawi yang ada di sanad dengan menggunakan kitab rija>l al-hadi>th versi mereka. Namun karena Shi’ah meyakini bahwa segala yang bersumber dari Imam bisa diterima sebagai hujjah, maka kritik terhadap matan tidak dilakukan dengan syarat kualitas sanad sudah sahih. Ketiga, implementasi kaedah kesahihan hadis berimplikasi pada kualitas hadis yang bertingkat, yaitu sahi>h, hasan, muwaththaq dan da’i>f.